Efficacy of National Nosocomial Infection Surveillance score, acutphase proteins, and interleukin-6 for predicting postoperative infections following major gastrointestinal surgery - Aguilar-Nascimento, José Eduardo de; Marra, Jair Gimenez; Slhessarenko, Natasha; Fontes, Cor Jesus Fernandes (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Postoperative infections should be detected earlier. We investigated the effi cacy of the National Nosocomial Infection Surveillance (NNIS) score, interleukin-6 (IL-6) and various acute-phase proteins for predicting postoperative infections. DESIGN AND SETTING: Case series study at the Júlio Müller University Hospital. METHODS: Thirty-two patients who underwent major gastrointestinal procedures between June 2004 and February 2005 were studied. The NNIS score and the evolution of serum IL-6 and various acute-phase proteins (C-reactive protein [CRP], albumin, prealbumin and transferrin) were correlated with postoperative infections and length of hospital stay (LOS). RESULTS: NNIS > 1 (p = 0.01) and low preoperative albumin (p = 0.02) signifi cantly correlated with infection. IL-6 and CRP increased signifi - cantly more in patients with infections. Multivariate analysis showed greater risk of infection when NNIS > 1 (odds ratio, OR = 10.66; 95% confi dence interval, CI: 1.1-102.0; p = 0.04); preoperative albumin < 3 g/dl (OR = 8.77; 95% CI: 1.13-67.86; p = 0.03); CRP > 30 mg/l on the second postoperative day (OR = 8.27; 95% CI: 1.05-64.79; p = 0.03) and > 12 mg/l on the fi fth postoperative day (OR = 25.92; 95% CI: 2.17-332.71; p < 0.01); and IL-6 > 25 pg/ml on the fi fth postoperative day (OR = 15.46; 95% CI: 1.19-230.30; p = 0.03). Longer LOS was associated with cancer, transferrin, IL-6 and albumin (p < 0.05). CONCLUSIONS: NNIS, albumin, CRP and IL-6 may be useful as predictive markers for postoperative infections. For predicting LOS, malignant condition, transferrin, albumin and IL-6 are useful.